The Influence of Flexible Working on Performance with Job Satisfaction as A Mediator on Lecturers with A Millennial Generation Background at the Timor University - Huda, Nurul; Aziz, Syaefudin; Korbaffo, Yesus (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research aims to determine the significance of the influence of flexible working on performance directly and indirectly, which is mediated by job satisfaction. The research method approach is quantitative, using primary data from questionnaires to 149 millennial lecturers at the University of Timor who were the research samples. The data obtained was then analyzed using the Partial Least Square (PLS) approach using the SmartPLS program. This research shows that flexible working directly significantly affects the job satisfaction of lecturers with millennial generation backgrounds at the University of Timor. Directly, job satisfaction also significantly affects the performance of lecturers with a millennial generation background at the University of Timor. Directly, flexible working does not significantly affect the performance of lecturers with a millennial generation background at the University of Timor. Indirectly, flexible working significantly affects the performance of lecturers with a millennial generation background at the University of Timor through job satisfaction as a mediating variable.